Fabrication And Structural Modification Of Graphene Oxide-tetraethyl Orthosilicate Solution Via Liquid-phase Pulsed Laser Ablation - Anne Tham; Kai Xin Siah; Ikhwan Mohd Noor; Ifwat Ghazali; Sin Tee Tan; Nizam Tamchek (AIP Publishing, 2025)
Indexed by Scopus